'Mitotherapy' for Heart Failure. Issue 4 (April 2016) - Sanchis-Gomar, Fabian; Lippi, Giuseppe; Lucia, Alejandro
Abstract : Abnormalities in mitochondrial dynamics along with those for the molecular mediators involved are presently being viewed with increased interest in the field of cardiovascular disease. Recent research highlights OPA1, a dynamin-like GTPase mediating mitochondrial fusion, as well as the 'mitoproteases' OMA1 and YME1L, as potential therapeutic targets against heart failure.